Optimization analysis on the support performance of composed anchor rod components in gob-side roadway - Yu, Jiang; Jin, Linlin; Ma, Hongfa; Zhang, Jun; Wang, Feng; He, Xin; Yin, Dawei (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2025)
In response to the failure problem of the roadway support structure for the deep buried mine, the mechanical calculation model was established based on the stress state and the boundary conditions of the composed anchor rod under the large surrounding rock deformation, and the failure discrimination criterion was obtained. Then a structural analysis unit for rock-composed anchor was established using ANSYS simulation software, which intensively researched the single-point and local failure characteristics of anchor rods in gob-side entries, and the optimization measures of the com-posed anchor rods were proposed. The findings reveal that the higher preload could restrain the axial displacement of the anchor rod, leading to stress concentration, fracture, or loosening of anchor bolts or nuts by the insufficient rock deformation. In addition, the stress concentration and plastic defor-mation of pallet orifice are significant as the main pressure-bearing part. The increase in the surround-ing rock deformation leads to an enhanced combined action of pressure and shear force between the steel strip and the pallet edge, which makes the steel strip prone to failure. Consequently, the optimiza-tion measures of reducing prestress and increasing the size of pallet and strip are proposed, which can effectively control the deformation of surrounding rock and reduce the stress concentration, plastic deformation and failure rate of composed anchor rod.
Mining Science, Vol. 32, 2025, s. 65-85
Keywords: górnictwo; geoinżynieria; geologia; gob-side entry; composed anchor rods; ANSYS; support performance